Netherlands : Selected Issues. (IMF Staff Country Reports; Country Report, 1997)
This Selected Issues paper examines Netherlands' experience with macroeconomic and structural reforms. The reforms, which were introduced gradually and in a consultative manner, were comprehensive in their coverage. They included a credible monetary policy, based on a tight link to the deutsche mark; expenditure-based fiscal consolidation, which allowed reduction of the tax burden as well as the fiscal deficit; and measures to stimulate both the supply and the demand side of the labor market. The labor market and associated social security reforms focused on measures to strengthen labor supply as well as labor demand.